Analisis aktivitas antioksidan ekstrak etanol daun jeruk kuok (Citrus nobilis L.) dengan metode DPPH (1,1-Diphenyl-2-Picrylhydrazyl) - Nurul Hasanah; Rafita Yuniart; Haris Munandar Nasution; Yayuk Putri Rahayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
When the body is excessively exposed to free radicals, the need for antioxidants increases as the body lacks sufficient protection. Some secondary metabolites in plants that can act as antioxidants include flavonoids, alkaloids, and tannins. This research aims to identify secondary metabolite compounds present in the raw material and extract of Citrus nobilis L. (kuok orange) leaves and evaluate antioxidant activity by determining IC50 values. This study employs several methods, including analyzing crude characteristics, phytochemical screening, and antioxidant activity testing using the DPPH (1,1-Diphenyl-2-picrylhydrazyl) method with spectrophotometry UV-Visible. The characterization results of the natural material indicate a water content of 6.66%, a water-soluble compound content of 19.64%, an ethanol-soluble compound content of 24.67%, a total ash content of 4.44%, and an acid-insoluble ash content of 0.66%. These findings align with values documented in the existing literature on MMI. Phytochemical screening results reveal that the crude material and ethanol extract of Citrus nobilis L. (kuok orange) leaves contain various chemical compounds, including alkaloids, flavonoids, saponins, tannins, glycosides, and steroids. The IC50 value for the ethanol extract of Citrus nobilis L. leaves is approximately 40.4587 g/mL, categorizing it as very strong. This indicates that the ethanol extract of Kuok orange leaves possesses secondary metabolite compounds with a highly potent antioxidant capability.